ENHANCING EMERGENCY HELPING ATTITUDES THROUGH ANIMATED BASIC LIFE SUPPORT EDUCATION AMONG ISLAMIC BOARDING SCHOOL ADOLESCENTS: A PRE-EXPERIMENTAL STUDY - Muhammad Malik Suryanto Suryanto; Vita Purnamasari; Triyas Singgih Pambudi (Keperawatan Anestesiologi Program Sarjana Terapan, 2026)
ABSTRACT Background: Cardiac arrest is a life-threatening emergency that requires immediate intervention through Basic Life Support (BLS) to improve survival outcomes. Adolescents in Islamic boarding schools may encounter emergency situations; however, their attitudes toward providing BLS assistance are often inadequate. Innovative educational media, such as animated videos, may enhance learning engagement and foster positive helping attitudes. This study aimed to determine the effect of animated Basic Life Support education on helping attitudes among adolescents at an Islamic boarding schooly Methods: A pre-experimental study with a one-group pretest–posttest design was conducted among 51 students of As-Sakinah Muhammadiyah 1 Islamic Boarding School, Yogyakarta. Participants were selected using purposive sampling. Helping attitudes toward BLS were measured using a structured questionnaire before and after the educational intervention. The intervention consisted of animated video-based BLS education. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p<0.05. Results: Prior to the intervention, most participants demonstrated moderate helping attitudes (74.5%), while 25.5% showed high helping attitudes. Following the intervention, all participants (100%) achieved a high level of helping attitude. Statistical analysis revealed a significant improvement in helping attitudes after the educational intervention (p=0.000), indicating that animated BLS education effectively enhanced participants’ willingness and readiness to provide assistance in emergency situations. Conclusion: Animated Basic Life Support education significantly improves helping attitudes among Islamic boarding school adolescents. The findings suggest that animated video-based education can serve as an effective strategy for increasing emergency preparedness and promoting positive bystander responses among adolescents. Future educational programs are encouraged to incorporate engaging digital media to strengthen Basic Life Support awareness and readiness.